Soybean flour induces a greater increase of the antioxidant defenses in rats fed with a normocaloric diet compared with a hypercaloric diet - Razetto, Gabriela S. (2015)
BACKGROUND: Soybeans, due to their antioxidant properties, present beneficial health effects. The objective was to evaluate if replacing casein with soy flour, modifies antioxidant defenses in rat liver, compared to animals that continued being fed with casein based diets (normocaloric and hypercaloric). RESULTS: Four groups of rats were used: CC (control casein), CS (control soy), HC (hypercaloric casein) and HS (hypercaloric soy). Malondialdehyde, in serum and liver, did not present differences. In liver, when comparing CS vs. CC: increased superoxide dismutase 1 (P < 0.001), catalase (P < 0.01) and glutathione reductase (P < 0.05) activities, the total glutathione (P < 0.001) and reduced glutathione (P < 0.05) content and decreased oxidized glutathione content (P < 0.05). In HS vs. HC: increased carbonyl groups (P < 0.01) and superoxide dismutase 1 activity (P < 0.05), and decreased glutathione peroxidase activity (P < 0.01), total glutathione (P < 0.05) and oxidized glutathione content (P < 0.001). In HS vs. CS: decreased glutathione reductase activity (P < 0.01), total glutathione (P < 0.001) and reduced glutathione (P < 0.01) content, and increased oxidized glutathione content (P < 0.05). CONCLUSION: Replacing casein by soybean flour improves antioxidant defenses, mainly in normocaloric diets.